Cognitive and psychophysiological correlates of disgust in obsessive‐compulsive disorder. (10th June 2014) - Whitton, Alexis E.; Henry, Julie D.; Grisham, Jessica R.
<x xml:space="preserve">Abstract</x> Objectives Evidence suggests that obsessive‐compulsive disorder (OCD) is characterized by heightened self‐reported disgust, however, it is unclear if this extends to physiology. The relationship between obsessive beliefs and disgust also remains poorly understood. Therefore, we examined whether the heightened trait and self‐reported disgust observed in individuals with OCD is reflected in heightened physiological disgust responses. We also examined whether obsessive beliefs are associated with disgust responding. Design A 3 (group) × 6 (stimulus) repeated measures design was used to examine disgust responses in individuals with OCD to six categories of image stimuli: body waste, contamination, injury, sociomoral, neutral, negative non‐disgust. Methods Individuals with OCD (n = 25) were compared to individuals with non‐OCD anxiety disorders (n = 21) and healthy participants (n = 25) with respect to trait, self‐reported, facial electromyographic and electrodermal disgust responses. Results Individuals with OCD showed greater disgust propensity and self‐reported disgust to images of body waste compared to healthy and anxious participants, however, there were no group differences in physiological responses. After controlling for trait disgust, obsessive beliefs positively correlated with increased self‐reported disgust to neutral images and increased levator labii activity to negative non‐disgusting images. Conclusions Although individuals with OCD showed elevated disgust propensity and self‐reported ratings of body waste stimuli, there was little evidence that OCD is characterized by an abnormal physiological disgust response. The intensity of obsessive beliefs was associated with a tendency to respond with disgust in contexts that are non‐disgusting, indicating that obsessive beliefs may be implicated in pathological disgust. Practitioner points Individuals with OCD display greater levels of disgust propensity and self‐reported disgust to images of body waste compared to healthy control participants and individuals with non‐OCD anxiety disorders. The abnormalities in self‐reported disgust observed in those with OCD do not extend to abnormalities in electrodermal activity or facial electromyographic responses. Maladaptive obsessive beliefs commonly associated with OCD predict heightened disgust in contexts where objective sources of disgust are absent, even after controlling for trait disgust. Maladaptive obsessive beliefs may therefore be implicated in pathological disgust. This study used a heterogeneous OCD sample and future research is needed to determine whether the observed effects are greater for those with primarily washing and contamination symptoms. Although group differences emerged in self‐reported disgust, further replications using measures of state anxiety are needed to rule out the possibility that heightened self‐reported disgust was confounded with co‐occurring fear or general negative affect.